Self efficacy perawat terhadap tingkat kepatuhan hand hygiene di ruang keperawatan kritis - Sawitri Abiad, Malaika; Imallah, Rosiana Nur; Kurniasih, Yuni (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2026)
Background: Hand hygiene compliance is a key step in preventing nosocomial infections, particularly in critical care units, which have a high risk of infection transmission. Nurses' compliance with the Five Moments of Hand Hygiene is influenced by several factors, one of which is self-efficacy, which is an individual's belief in their ability to consistently perform the action. Purpose: To determine the relationship between nurses' self-efficacy and hand hygiene compliance levels in critical care units. Method: This was a quantitative cross-sectional study using a descriptive correlational approach. A sample of 51 nurses was selected through purposive sampling. Data were collected using a self-efficacy and hand hygiene compliance questionnaire. The relationship was analyzed using the Spearman Rank correlation test. Results: The majority of nurses had high self-efficacy (96.1%) and 92.2% of their hand hygiene compliance was compliant. A significant relationship was found between self-efficacy and hand hygiene compliance (p = 0.024) with a correlation coefficient of 0.317, indicating a positive relationship ranging from weak to moderate. Conclusion: Nurses' self-efficacy was significantly associated with hand hygiene compliance. Nurses with higher self-efficacy tend to be more compliant in implementing the Five Moments of Hand Hygiene. Keywords: Compliance; Five Moments; Hand Hygiene; Nurses; Self-Efficacy. Pendahuluan: Kepatuhan Hand hygiene merupakan langkah utama dalam pencegahan infeksi nosokomial, terutama di ruang perawatan kritis yang memiliki risiko tinggi penularan infeksi. Kepatuhan perawat dalam menerapkan Five Moments Hand Hygiene dipengaruhi oleh beberapa faktor, salah satunya adalah self efficacy, yakni keyakinan individu terhadap kemampuan diri dalam melaksanakan tindakan secara konsisten. Tujuan: Untuk mengetahui hubungan antara self efficacy perawat dengan tingkat kepatuhan hand hygiene di ruang keperawatan kritis. Metode: Penelitian kuantitatif cross-sectional dengan pendekatan deskriptif korelasional. Sampel berjumlah 51 perawat yang dipilih melalui purposive sampling. Data dikumpulkan menggunakan kuesioner self efficacy dan kepatuhan hand hygiene. Analisis hubungan menggunakan uji korelasi Spearman Rank. Hasil: Mayoritas perawat memiliki self efficacy tinggi (96.1%) dan kepatuhan hand hygiene kategori patuh (92.2%). Hubungan signifikan antara self efficacy dan kepatuhan hand hygiene sebesar (p = 0.024) dengan koefisien korelasi 0.317 yang menunjukkan hubungan positif dengan kekuatan lemah menuju sedang. Simpulan: Self efficacy perawat berhubungan signifikan dengan kepatuhan hand hygiene. Perawat dengan self efficacy lebih tinggi cenderung lebih patuh dalam melaksanakan Five Moments Hand Hygiene. Keywords: Five Moments; Hand Hygiene; Kepatuhan; Perawat; Self Efficacy